Organ-specific microplastic accumulation and particle-size distribution in fishes from Jepara, Central Java, Indonesia - RIZKI SANDHI TITISARI; RASYIDAH FAUZIA AHMAR; HERNANDA AFRA HANIYYAH; NADA AHMAD RAYHAN; LAILY ISROFIANI (Society for Indonesian Biodiversity, 2026)
Abstract. Titisari RS, Ahmar RF, Haniyyah HA, Rayhan NA, Isrofiani L. 2026. Organ-specific microplastic accumulation and particle-size distribution in fishes from Jepara, Central Java, Indonesia. Biodiversitas 27 (8): d270801. https://doi.org/10.13057/biodiv/d270801. Microplastic contamination is increasingly reported in coastal environments, yet organ-specific burdens and particle characteristics in fishes from Indonesian nearshore systems remain limited. This study quantified organ-specific, including gills, stomach, intestine, liver and kidney microplastic accumulation and particle-size distributions in fishes from Jepara District, Central Java, Indonesia, comparing an aquaculture-associated site (Teluk Awur) with a comparative coastal site (Bandengan) during June-July 2025 (Teluk Awur, n: 9; Bandengan, n: 13). Fish were dissected immediately after capture, and suspected microplastics were assessed in gills, stomach, intestine, liver, and kidney following H₂O₂ digestion, ZnCl₂ density separation, vacuum filtration, and stereomicroscope observation. Particles were morphologically classified and measured using FIJI. Differences among organs were assessed using the Friedman test, and between-site comparisons used the Mann-Whitney U test. Suspected microplastics were detected in all examined organs across all sampled fishes (100% prevalence). Organ burdens indicated gastrointestinal dominance at Teluk Awur, whereas pooled wild-caught taxa showed more variable organ profiles, reflecting species assemblage rather than a single biological response pattern, including elevated internal-organ loads in several taxa. Morphologically, fragments dominated at both sites, while Teluk Awur showed relatively higher contributions of flakes and fibers and Bandengan showed higher contributions of microbeads, pigments, and films. Overall, these results constitute a descriptive, organ-resolved baseline snapshot of sMPs burdens in Jepara fishes during June-July 2025, providing a reference framework for future biomonitoring and seafood-safety assessments at these sites.